Intrafloral Color Modularity in a Bee-Pollinated Orchid - Aguiar, João Marcelo Robazzi Bignelli Valente; Maciel, Artur Antunes; Santana, Pamela Cristina; Telles, Francismeire Jane; Bergamo, Pedro Joaquim; Oliveira, Paulo Eugênio; Brito, Vinicius Lourenço Garcia (Frontiers in Plant Science, 2020)
Flower color has been studied in different ecological levels of organization, from individuals to communities. However, it is unclear how color is structured at the intrafloral level. In bee-pollinated flowers, the unidirectional gradient in color purity and pollen mimicry are two common processes to explain intrafloral color patterns. Considering that floral traits are often integrated, usually reflecting evolutionary modules under pollinator-mediated selection, we hypothesize that such intrafloral color patterns are structured by intrafloral color modules. Here, we studied the tropical bee-pollinated orchid Cattleya walkeriana, given its intrafloral color complexity and variation among individuals. We investigated if intrafloral color modules arose among intrafloral patches (tip or base of the sepals, petals, and labellum). We expected a separate color module between the labellum patches (the main attractive structure in orchids), i.e. varying independently among individuals in relation to petals and sepals. We measured the color reflectance and calculated the spectral purity, hue, and the chromatic contrast of the floral structures. Spectral purity (saturation) was higher in the labellum tip in comparison to petals and sepals, generating a unidirectional gradient. Labellum base presented a less saturated yellow UV-absorbing patch, which may reflect a pollen mimicry strategy. The colors of tips and bases of petals and sepals were strongly correlated among individuals, forming a module, and weakly correlated with the tip of the labellum. There was no correlation between the color of the labellum base and any other floral patch. The color modules were unrelated to the development of floral whorls since the color of petals and sepals were integrated, while the labellum showed two different color modules. Given the importance of intrafloral color patterns in bee attraction and guidance, our results suggest that intrafloral patterns could be the outcome of evolutionary color modularization under pollinator-mediated selection.